Existentialist Feminism in Furiosa A Mad Max Saga: Women’s Struggle Beyond Patriarchal Domination - Alexander Wirija; Irma Rahmawati (Calakan : Jurnal Sastra, Bahasa, dan Budaya, 2025)
This research explores the existentialist feminist representation of women in Furiosa: A Mad Max Saga (2024), focusing on their struggle to reclaim subjectivity and resist patriarchal domination. Grounded in Simone de Beauvoir’s existentialist feminism, the research analyzes how female characters navigate a dystopian world controlled by male authority. Core concepts such as the Other, immanence, transcendence, freedom, and responsibility are used to interpret the journey of women from oppression to empowerment. This research employs a descriptive qualitative method, analyzing selected scenes, character development, dialogues, and cinematic techniques. While Furiosa is the central figure, the analysis also includes secondary female characters such as Mary Jabassa, Norton, and the Wives. The findings show that women are frequently treated as commodities or silenced objects, as depicted through scenes of confinement, trade, and suppression. However, the film also portrays acts of resistance, where women assert their agency through courage, strategy, and solidarity. Furiosa’s transformation from being objectified as “the Other” to achieving autonomy through transcendence, exemplifies the existential journey toward subjectivity. This research concludes that Furiosa: A Mad Max Saga challenges traditional gender norms in the action and science fiction genres, offering a meaningful contribution to feminist film criticism and existentialist feminist analysis.